Implementasi Metode Qiroati Terhadap Kemampuan Membaca Al-Qur’an Di MTS Tahfizh Al-Falakiyah Kota Bogor - Ratu Siti Naila Muna (KOLONI, 2024)
The Qiroati method is a model for learning to read the Al-Quran directly (without spelling it) and using or applying the habit of reading tartil according to the rules of recitation. The qiroati method is a fast and precise method for learning to read and write the Koran. This research aims 1) to determine the implementation of the Qiraati method on the ability to read the Al-Quran, 2) to determine the supporting and inhibiting factors for implementing the Qiraati method in reading the Al-Quran, 3) to find out solutions to the factors inhibiting the implementation of the Qiraati method in reading the Al-Quran -Quran -Quran. The research method uses qualitative methods where researchers will go directly to the field to observe events and facts that occur in the field. Test the validity of the data using triangulation techniques and data analysis using Mile and Huberman's interactive analysis, namely data collection, data reduction, data presentation and verification conclusions. The research results show that 1) the application of the qiroati method to the ability to read the Al-Quran has three steps, namely planning, implementation and individual evaluation. 2) there are several supporting factors, one of which is support from the school in accordance with the vision and mission, criteria and external motivation and there are several inhibiting factors, one of which is teacher development in teaching and learning media such as audio or video. 3) the solution to the inhibiting factors is regular training and development for the teaching team, complete learning tools and motivating students to learn by providing rewards.